Discovery and Characterization of a High-Affinity Small Peptide Ligand, H1, Targeting FGFR2IIIc for Skin Wound Healing - Ying Zhao (Cellular Physiology and Biochemistry, 2018)
Background/Aims: How to aid recovery from severe skin injuries, such as burns, chronic or radiation ulcers, and trauma, is a critical clinical problem. Current treatment methods remain limited, and the discovery of ideal wound-healing therapeutics has been a focus of research. Functional recombinant proteins such as basic fibroblast growth factor (bFGF) and epidermal growth factor (EGF) have been developed for skin repair, however, some disadvantages in their use remain. This study reports the discovery of a novel small peptide targeting fibroblast growth factor receptor 2 IIIc (FGFR2IIIc) as a potential candidate for skin wound healing. Methods: A phage-displayed peptide library was used for biopanning FGFR2IIIc-targeting small peptides. The selected small peptides binding to FGFR2IIIc were qualitatively evaluated by an enzyme-linked immunosorbent assay. Their biological function was detected by a cell proliferation assay. Among them, an optimized small peptide named H1 was selected for further study. The affinity of the H1 peptide and FGFR2IIIc was determined by an isothermal titration calorimetry device. The ability of theH1 peptide to promote skin wound repair was investigated using an endothelial cell tube formation assay and wound healing scratch assay in vitro. Subsequently, the H1 peptide was assessed using a rat skin full-thickness wound model and chorioallantoic membrane (CAM) assays in vivo. To explore its molecular mechanisms, RNA-Seq, quantitative real-time PCR, and western blot assays were performed. Computer molecular simulations were also conducted to analyze the binding model. Results: We identified a novel FGFR2IIIc-targeting small peptide, called H1, with 7 amino acid residues using phage display. H1 had high binding affinity with FGFR2IIIc. The H1 peptide promoted the proliferation and motility of fibroblasts and vascular endothelial cells in vitro. In addition, the H1 peptide enhanced angiogenesis in the chick chorioallantoic membrane and accelerated wound healing in a rat full-thickness wound model in vivo. The H1 peptide activated both the PI3K-AKT and MAPK-ERK1/2 pathways and simultaneously increased the secretion of vascular endothelial growth factor. Computer analysis demonstrated that the model of H1 peptide binding to FGFR2IIIc was similar to that of FGF2 and FGFR2IIIc. Conclusion: The H1 peptide has a high affinity for FGFR2IIIc and shows potential as a wound healing agent. As a substitute for bFGF, it could be developed into a novel therapeutic candidate for skin wound repair in the future.